Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Guru Pada MAN 1 Pesisir Barat - Hairudin Hairudin; eka travilta oktaria; Wenda Wenda (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
This study sought to ascertain how the work environment and stress at MAN 1 Pesisir Barat affected instructors' performance in part and simultaneously. This study's methodology uses a quantitative approach. Questionnaires and observation are the two methods of data collecting. Using a Likert Scale for each statement derived from the indicator variable, research variables are measured. 54 teachers made up the study's sample, which was selected using a non-probability sampling method. To support the hypothesis, data analysis techniques used statistical methods such multiple linear regression analysis with F-test and t-test, as well as validity and reliability checks for surveys. The findings demonstrated a beneficial and significant impact of both the work environment and job stress on teacher performance at MAN 1 Pesisir Barat. In addition, while the work environment has a good and considerable impact on teachers' performance at MAN 1 Pesisir Barat, job stress has a limited impact on that performance. The MAN 1 Pesisir Barat school administration must pay attention and enhance the current working conditions in order to maximize teacher effectiveness.